Effect of some cultural practices on the growth and yield of the medicinal plant Solanum virginianum schrad (Katuwelbatu) - Pathiratna L S S; Joseph K D S M; Perera M K P (Ceylon Journal of Science (Bio.Sci), 2004)
Experiments were conducted to study the effect of inorganic, organic and combined inorgaic + organic fertilizer and natural shade under Gliricidia on the growth and dry matter (DM) yield of the medicinal plant Solanum virginianum schrad. The yield of total dry matter and of different plant parts were also studied in plants harvested at 70, 90 and 110 days after establishment. Application of cow dung as organic fertilizer as the basal at a rate of 15,000 kg/ha plus a dose of inorganic fertilizer (12:9:8 N:P:K) at a rate of 200 kg/ha after one month gave the highest DM yields compared to organic fertilizer only at the rate of 25,000 kg/ha or inorganic fertilizer only at the rate of 400kg/ha both as basal. The type of the fertilizer package used also affected the composition of leaves, stems and berries in plants. DM yields were low in plants harvested at 70 days. Higher DM yields obtained from plants harvested at 90 and 110 days were mostly due to the presence of more berries. Shade always reduced the DM yield of plants and the reductions were 40.6;and 57.6;under 58.0;and 45.0;available light respectively.
Keywords: Dry matter; Harvesting time; Shade; Solanum virginianum